Os três ensaios sobre a teoria da sexualidade de Sigmund Freud e a psicologia da criança no final do século XIX - Almeida, Alexandra Nakano de (2006)
In this research, we try to understand the infantile concept for Sigmund Freud, at the end of the XIXth century and beginning of the XXth, by studying Three essays on the theory of sexuality (1905) in which the author presents his theory of the infantile sexuality. For this reason, we have investigated Freud s background and course, as well as the creation of psychoanalysis, in order to identify the author s conjectures to elaborate this theory, formalized in 1905. The theory of infantile sexuality, by Sigmund Freud took shape, starting mainly from problems and hypotheses occurred during his clinical activities, or otherwise, beginning from his attempts to elucidate and treat the hysteria phenomenon. Thus, the freudian idea of infantile was conceived by observing the adult and not the child. At the end of the XIXth century and beginning of the XXth, period during which Sigmund Freud developed the theory of infantile sexuality we may see that there is an increasing valorization of children and childhood as subject for psychological studies. Thus, in this research, we generally look forward to define the main concerns of these children s psychological studies, in order to contextualize the freudian theory formulation and check the possible relationship, between the emergency of this knowledge, which considers the child as an investigation object, and the freudian theory on infantile sexuality